2006
DOI: 10.1175/mwr3188.1
|View full text |Cite
|
Sign up to set email alerts
|

Corridors of Warm Season Precipitation in the Central United States

Abstract: During the warm season in the central United States there often exists a corridor of precipitation where a succession of mesoscale convective systems (MCSs) follow similar paths lasting several days. The total cumulative rainfall within a corridor can be substantial while precipitation at nearby regions may be below normal. Understanding the nature of the corridors and the environmental factors important for their formation thus has important implications for quantitative precipitation forecasting and hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 42 publications
(46 reference statements)
11
90
0
Order By: Relevance
“…Thus, the primary rainfall axes are more representative of all 23 cases than the secondary axes. The primary rainfall axis is similar to that observed in studies examining longer time periods (e.g., Carbone et al 2002;Tuttle et al 2006), while the secondary axis has not been observed in the studies examining the longer time periods. However, Clark et al (2007) did observe a secondary rainfall axis during Feb -Apr 2007 over the northern portion of the central US.…”
Section: A Analysis Of Diurnally-averaged Hovmöller Diagramssupporting
confidence: 79%
“…Thus, the primary rainfall axes are more representative of all 23 cases than the secondary axes. The primary rainfall axis is similar to that observed in studies examining longer time periods (e.g., Carbone et al 2002;Tuttle et al 2006), while the secondary axis has not been observed in the studies examining the longer time periods. However, Clark et al (2007) did observe a secondary rainfall axis during Feb -Apr 2007 over the northern portion of the central US.…”
Section: A Analysis Of Diurnally-averaged Hovmöller Diagramssupporting
confidence: 79%
“…The latitude 38°N was chosen to separate the domain into two halves because the corridor in which propagating rainfall systems occurred most frequently was roughly the northern half of the full domain. The tendency for propagating systems to concentrate in latitudinal corridors has been documented by Tuttle and Davis (2006). This partitioning led to diurnally averaged Hovmöller diagrams of observed rainfall with the propagating (nonpropagating) rainfall axis having the higher amplitude in the northern (southern) portion of the analysis domain.…”
Section: Comparison Of Hovmöller Diagrams For the North And South mentioning
confidence: 94%
“…At least observationally this includes the pursuit of a better understanding of storm environmental attributes that are characteristic of high-end wind storms. Coniglio et al (2011) found that the primary difference between the 8 May 2009 derecho environment and a more general mesoscale convective system (MCS; Houze 2004) environment was a strong and deep lowlevel jet (Tuttle and Davis 2006) that was transporting anomalously high mixing ratio air toward the storm underneath anomalously large midtropospheric lapse rates. Interestingly, these ingredients are primarily promoting stronger updrafts, rather than stronger downdrafts.…”
Section: Introductionmentioning
confidence: 99%